2016
DOI: 10.1093/nar/gkw949
|View full text |Cite
|
Sign up to set email alerts
|

Expanded national database collection and data coverage in the FINDbase worldwide database for clinically relevant genomic variation allele frequencies

Abstract: FINDbase (http://www.findbase.org) is a comprehensive data repository that records the prevalence of clinically relevant genomic variants in various populations worldwide, such as pathogenic variants leading mostly to monogenic disorders and pharmacogenomics biomarkers. The database also records the incidence of rare genetic diseases in various populations, all in well-distinct data modules. Here, we report extensive data content updates in all data modules, with direct implications to clinical pharmacogenomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Population pharmacogenomic research has shown that the study of pharmacogenomic markers in various populations is of great importance. Comprehensive data repositories that record the prevalence of clinically relevant genomic variants in populations worldwide, including pharmacogenomic biomarkers, are valuable tools that can be exploited not only to develop guidelines for medical prioritization, but most importantly, to facilitate integration of pharmacogenomics into health care systems and to support preemptive pharmacogenomic testing [ 27 ]. UGT1A1 (TA) n promoter genotypes resulting in decreased function of the UGT1A1 enzyme are pharmacogenomic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Population pharmacogenomic research has shown that the study of pharmacogenomic markers in various populations is of great importance. Comprehensive data repositories that record the prevalence of clinically relevant genomic variants in populations worldwide, including pharmacogenomic biomarkers, are valuable tools that can be exploited not only to develop guidelines for medical prioritization, but most importantly, to facilitate integration of pharmacogenomics into health care systems and to support preemptive pharmacogenomic testing [ 27 ]. UGT1A1 (TA) n promoter genotypes resulting in decreased function of the UGT1A1 enzyme are pharmacogenomic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the previous FINDbase data content updates in 2010 (Georgitsi et al, 2011a;2011b), 2013 (Papadopoulos et al, 2014) and 2016 (Viennas et al, 2017), the current content update did not only include data curation, updates, and corrections, but also extensive data enrichment. In particular, FINDbase data collection was enriched mostly with PGx biomarker allele frequencies, derived from two large genotyping efforts that evaluated the prevalence of clinically actionable PGx biomarkers in more than 20, mostly European, populations (see Mizzi et al, 2016;Patrinos et al, 2012;Petrović, Pešić, & Lauschke, 2020).…”
Section: Data Content Enrichmentmentioning
confidence: 94%
“…FINDbase has the most extensive content among all current NEGDBs and constitutes one of the key resources for population-specific clinically relevant genomic variation allele frequency data information deducted from the number and origin of visitors, while it also complies with the recommendations for genomic data collection from populations (Patrinos et al, 2011). To keep FINDbase up-to-date and user-friendly, its user interface and querying module have undergone major refurbishments and updates in 2010 (Georgitsi et al, 2011b), while its data content is being continuously enriched and updated, where needed, in response to user feedback (Papadopoulos et al, 2014;Viennas et al, 2017). Still, the continuous data updates and influx dictated further upgrade of the user interface so that data output is expedited and provided in a timely manner.…”
Section: Introductionmentioning
confidence: 97%
“…GMA members have actively participated in the development of new or the update of existing National/Ethnic Genetic databases for several populations in GMA member territories, such as Greece, Serbia, Kuwait, Egypt and Tunisia, using the newly upgraded ETHNOS software [Viennas et al, 2017].…”
Section: Genome Informatics Working Groupmentioning
confidence: 99%